1990
DOI: 10.1007/bf00846029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of age and regular exercise on muscle strength and endurance

Abstract: Twenty male and 20 female non-professional tennis players were classified into two different age groups (n = 10 per group): young active men (30.4 +/- 3.3 years), young active women (27.5 +/- 4.3 years), elderly active men (64.4 +/- 3.7 years), and elderly active women (65.3 +/- 4.5 years). These individuals were matched (n = 10 per group) according to sex, age, height and mass to sedentary individuals of the same socio-economical background: young sedentary men (29.2 +/- 3.4 years), young sedentary women (25.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
1
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(85 citation statements)
references
References 33 publications
7
76
1
1
Order By: Relevance
“…These findings of no agerelated difference in fatigability of the knee extensors resemble most (Laforest et al 1990;Lindstrom et al 1997;Deschenes et al 2008;Callahan et al 2009;Callahan and Kent-Braun 2011;Dalton et al 2012), but not all previous studies in this muscle group (Rawson 2010;Callahan and Kent-Braun 2011). Greater age-related differences emerged only at the faster velocities (Callahan and Kent-Braun 2011), but these velocities of typically between 90°and 270°s are not fast for angular knee extensions (Dalton et al 2012;Thompson et al 2014).…”
Section: Task Failuresupporting
confidence: 65%
See 1 more Smart Citation
“…These findings of no agerelated difference in fatigability of the knee extensors resemble most (Laforest et al 1990;Lindstrom et al 1997;Deschenes et al 2008;Callahan et al 2009;Callahan and Kent-Braun 2011;Dalton et al 2012), but not all previous studies in this muscle group (Rawson 2010;Callahan and Kent-Braun 2011). Greater age-related differences emerged only at the faster velocities (Callahan and Kent-Braun 2011), but these velocities of typically between 90°and 270°s are not fast for angular knee extensions (Dalton et al 2012;Thompson et al 2014).…”
Section: Task Failuresupporting
confidence: 65%
“…Studies that used constrained velocity (i.e., isokinetic) tasks and thus defined fatigue as a loss of torque have reported the same (Laforest et al 1990;Callahan et al 2009;Dalton et al 2012), less (Lanza et al 2004;Rawson 2010), or more (Baudry et al 2007;Callahan and Kent-Braun 2011) fatigue in older adults compared with young. Explaining the variability among these studies that used isokinetic tasks, and in comparison with those that have used isotonic tasks, is challenging due to the range of angular velocities tested.…”
Section: Introductionmentioning
confidence: 99%
“…Maughan et al (1986) reported that muscle endurance was higher in females in loads below 70% MVC, but there is not a gender difference in loads above 80% MVC. Laforest et al (1990) reported that there were not gender differences in force values during maximal work. Therefore, in the sustained force exertion of submaximal workload below 70% MVC, physical fatigue by force exertion may differ between males and females.…”
Section: Discussionmentioning
confidence: 97%
“…Muscle endurance, until now, has been mainly evaluated by sustaining time or decreasing rate using fixed, relative load intensities (Maughan et al 1986;Laforest et al 1990;Clarke et al 1992;Huczel et al 1992;Larsson et al 2003). When using very large loads, the exerted force decreases markedly just after initiating force exertion, blood pressure and heart rate increase, and also the sensation of muscle pain increases (Petrofsky and Hendershot 1984).…”
Section: © 2008 Tohoku University Medical Pressmentioning
confidence: 99%
See 1 more Smart Citation